Los verbos prefijados cultos (español, portugués y catalán) o el fracaso de la morfología - García-Medali, Joaquín (Studia Romanica Posnaniensia, 2004)
All the Romance languages (of course, Spanish, Portuguese and Catalan, too), contain a group of verbs which are not sensitive to a compositional analysis of their morphemes in terms of lexical semantics. But, at the same time, they are susceptible to a formal analysis. I call them "configurational verbs", as esp. conducir, aducir, deducir, reducir, etc. In this paper, I'll try to describe first the similiarities and differences among the configurational verbs of these languages in relation to their form, and then their syntactical behaviour in terms of expanded phrases.